Efficacy and Safety of Varenicline for Adolescent Smoking Cessation - Mochamad Taufik, Mochamad Taufik; Bambang, Bambang (International Medical Journal Corp. Ltd, 2024)
Background: The literature on the efficacy and safety of varenicline for adolescent smoking cessation presents a complex interplay of pharmacological mechanisms, clinical implications, and developmental considerations. Literature Review: The safety profile of varenicline remains a significant concern, particularly in populations under 18. Studies indicate that while varenicline is generally well tolerated in older adults, its safety in adolescents is less clear due to a lack of targeted research (Robson, 2010). The systematic review by (J Prochaska & F Hilton, 2012) highlights cardiovascular risks associated with varenicline but notably excludes adolescent studies, indicating a gap in understanding how these risks translate to younger populations. This absence of data raises questions about the applicability of findings from adult populations to adolescents, who may have different physiological and psychological responses to pharmacotherapy. Conclusion: Overall, while varenicline demonstrates potential as an effective smoking cessation aid for adolescents, the existing literature underscores the need for further research to address safety concerns and to explore its efficacy in this unique population. A comprehensive understanding of both pharmacological effects and developmental considerations is necessary to inform clinical practice and enhance smoking cessation efforts among adolescents.